Boronic ionogel electrolytes to improve lithium transport for Li-ion batteries. (10th October 2016) - Lee, Albert S.; Lee, Jin Hong; Hong, Soon Man; Lee, Jong-Chan; Hwang, Seung Sang; Koo, Chong Min
Abstract: Boron containing ionogels were fabricated through chemical crosslinking of boron allyloxide with polyethylene glycol dimethacrylate in an ionic liquid electrolyte solution to obtain mechanically robust gels. Because of the relatively small concentration of crosslinking agent required to fully solidify the ionic liquid electrolyte, good characters of high ionic conductivity, high thermal stability, and good electrochemical stability were observed. A spectroscopic investigation of the boronic ionogels revealed that the lithium mobility was noticeably enhanced compared with ionogels fabricated without the boronic crosslinker, leading to promising Li-ion battery performance at elevated temperatures.